2019
DOI: 10.1063/1.5132954
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature electron mobility exceeding 104 cm2/V s in MOCVD grown β-Ga2O3

Abstract: We report on record electron mobility values measured in lightly Si doped homoepitaxial β-Ga2O3 grown by metal-organic chemical vapor deposition. The transport properties of the films were studied using temperature-dependent Hall measurements. Numerous (010) β-Ga2O3 layers grown at different conditions showed peak electron mobility exceeding 104 cm2/V s at low temperature (LT), with the highest value of 11 704 cm2/V s at 46 K. The room temperature electron mobilities of the films were between 125 cm2/V s and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…RT and low‐temperature electron μ reached 180 and 11 000 cm 2 V s −1 , respectively. [ 40–42 ] These electrical properties are comparable with those of HVPE‐grown n‐Ga2normalO3 films. Moreover, the growth rate, which used to be very slow at 0.1–0.2 μm h −1 , was enhanced to >3 μm h −1 .…”
Section: Epitaxial Thin‐film Growth Of β-Ga2normalo3supporting
confidence: 52%
“…RT and low‐temperature electron μ reached 180 and 11 000 cm 2 V s −1 , respectively. [ 40–42 ] These electrical properties are comparable with those of HVPE‐grown n‐Ga2normalO3 films. Moreover, the growth rate, which used to be very slow at 0.1–0.2 μm h −1 , was enhanced to >3 μm h −1 .…”
Section: Epitaxial Thin‐film Growth Of β-Ga2normalo3supporting
confidence: 52%
“…[15][16][17] So far, MOCVD (010) β-Ga 2 O 3 exhibited high-quality epitaxy with RT Hall mobility > 170 cm 2 /V•s. [4,[18][19][20] Our previous work has demonstrated RT mobility value of 184 cm 2 /V•s on lightly Si-doped (010) thin film with an extracted low-compensation level at N A < 10 15 cm -3 . [4] The full bandgap defect state scanning via deep level transient spectroscopy/deep level optical spectroscopy (DLTS/DLOS) on our MOCVD β-Ga 2 O 3 also confirmed one order lower of total defect density as compared with bulk material or thin films grown by other techniques.…”
Section: Author Manuscriptmentioning
confidence: 96%
“…[21] Most recently, RT mobility of 130 cm 2 /V•s and low temperature (LT) peak mobility of 11700 cm 2 /V•s were reported for MOCVD grown Si-doped β-Ga 2 O 3 thin films. [19] As compared with other wide bandgap semiconductors such as SiC and GaN, the extrodinary high LT mobility in β- Among the best reported MOCVD β-Ga 2 O 3 , the n-type background concentration ranged between 10 15 cm -3 and low-10 16 cm -3 . [4,[18][19][20] The measured background carrier concentration is a result of unintentional n-type doping and low-compensation (N A ) level.…”
Section: Author Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies on the temperature-dependent states indicated a two-donor level, with a shallower donor energy level (ED1 = ∼10 − 35 meV) and deeper second donor (ED2 = ∼80 − 100 meV) energy levels [49][50][51]. Si is a common n-type dopant in β-Ga2O3 [52], which is predicted by the first principle of density functional theory (DFT) [53] to be a shallow donor with its preference site as a tetrahedral site Ga(I) under oxygen-rich condition due to a lower formation energy.…”
Section: Nomentioning
confidence: 99%